Inhibition of H1N1 influenza virus infection by zinc oxide nanoparticles: another emerging application of nanomedicine - Ghaffari, Hadi (J Biomed Sci, 2019)
BACKGROUND: Currently available anti-influenza drugs are often associated with limitations such as toxicity and the appearance of drug-resistant strains. Therefore, there is a pressing need for the development of novel, safe and more efficient antiviral agents. In this study, we evaluated the antiviral activity of zinc oxide nanoparticles (ZnO-NPs) and PEGylated zinc oxide nanoparticles against H1N1 influenza virus. METHODS: The nanoparticles were characterized using the inductively coupled plasma mass spectrometry, x-ray diffraction analysis, and electron microscopy. MTT assay was applied to assess the cytotoxicity of the nanoparticles, and anti-influenza activity was determined by TCID50 and quantitative Real-Time PCR assays. To study the inhibitory impact of nanoparticles on the expression of viral antigens, an indirect immunofluorescence assay was also performed. RESULTS: Post-exposure of influenza virus with PEGylated ZnO-NPs and bare ZnO-NPs at the highest non-toxic concentrations could be led to 2.8 and 1.2 log10 TCID50 reduction in virus titer when compared to the virus control, respectively (P < 0.0001). At the highest non-toxic concentrations, the PEGylated and unPEGylated ZnO-NPs led to inhibition rates of 94.6 and 52.2%, respectively, which were calculated based on the viral loads. There was a substantial decrease in fluorescence emission intensity in viral-infected cell treated with PEGylated ZnO-NPs compared to the positive control. CONCLUSIONS: Taken together, our study indicated that PEGylated ZnO-NPs could be a novel, effective, and promising antiviral agent against H1N1 influenza virus infection, and future studies can be designed to explore the exact antiviral mechanism of these nanoparticles.